Polycladida (Platyhelminthes, Rhabditophora) from Cape Verde and related regions of Macaronesia - Cuadrado, Daniel; Rodríguez, Jorge; Moro, Leopoldo; Grande, Cristina; Noreña, Carolina (European Journal of Taxonomy, 2021)
The systematics and distribution of the order Polycladida within the Macaronesian archipelagos are analysed. New species (Marcusia alba sp. nov., Prostheceraeus crisostomum sp. nov., Parviplana sodade sp. nov., Euplana claridade sp. nov., Stylochus salis sp. nov. and Distylochus fundae sp. nov.), new variety (Pseudoceros rawlinsonae var. galaxy), new records and records of shared species among different archipelagos are studied to compare the marine flatworm biodiversity of each island. The complex of archipelagos known as Macaronesia (including Madeira, Selvagens Islands, Canary Islands, Azores and Cape Verde) share a volcanic origin and European political influence. The five archipelagos are located along the eastern coast of the Atlantic Ocean and are subject to similar trade winds, streams (like the Gulf Stream) and cold currents. The term Macaronesia has suffered several changes throughout the years and it still is a topic of discussion in present times. The new delimitation of Macaronesia is mainly based on systematic studies on the invertebrate fauna of the islands. The resulting analyses shed new light on the differences and similarities among these archipelagos. In addition, molecular analyses employing 28S nuclear gene sequences are compared to verify relationships among anatomically similar species of marine polyclads.